Incidence and causes of repeat breeding in crossbred dairy cows - a retrospective study - SELVARAJ, P; KUMAR, HARENDRA; BHIST, G S (The Indian Journal of Animal Reproduction, 2023)
The data for the present study were collected from Military Dairy Farm, Bareilly for a period of 10 years and the effect of season, parity, breed, milk yield and periparturient diseases on incidence of repeat breeding (RB) were analysed. The overall incidence of RB in Friesian x Sahiwal crossbred cows was 28.38 percent. The incidence was higher in spring calved than other seasons. The incidence of RB was also found higher (35.68%) during second than other parities. An increased incidence of RB was recorded in higher crosses (7/16, 5/8 and 3/4) and high yielders (36.10%). Abnormal calvings had significant influence on incidence of RB.